SISTEM KERJA LOAD SHEDDING DI POWER PLANT TALANG JIMAR PRABUMULIH FIELD - Sheylin Wimora Lumban Tobing (LPPM Universitas Pramita Indonesia, 2023)
Any interruption in the supply of vital energy can damage the entire system and simultaneously can damage the entire system and can paralyze daily activities. In Indonesia, there is almost no area that is not affected by load shedding. Insufficient electricity production is the main reason which means power generation is less than demand. The solution in minimizing the occurrence of disturbances and causing the electrical system to experience unstable voltage and frequency drops, is anticipated by carrying out a load shedding scenario, namely releasing excess load on one of the systems in order to reduce further impacts. Seeing the many disturbances that occur in the electricity sector in Indonesia, to see the load shedding system that exists in Indonesia, a study was carried out in one of the regions in Indonesia, namely at PT Pertamina Hulu Rokan Zone 4 Prabumulih Field. The load shedding system at PT Pertamina Hulu Rokan is by understanding the load shedding program at the Talang Jimar Power Plant, changing the generator maximum value, load shedding trigger and load shedding algorithm and load shedding configuration.